Preisschocks bei Energie und Nahrungsmitteln; Energy and food price shocks in the euro area - Silke Tober (Wirtschaftsdienst, 2022)
– The sharp revisions in inflation forecasts are not rooted in analytical flaws, overly hesitant ECB policies or model failures. Energy price shocks of historic dimensions are the key factor. They have ended the prolonged phase of excessively weak inflation with risks now clearly increasing. In contrast to the United States, the euro area shows no signs of overheating or excessive wage increases. Provided second-round effects remain muted, the ECB should proceed gradually given the high war-related uncertainty and the energy-cost related drag on the economy. Monetary policy flexibility is of key importance particularly with regards to sovereign yield differentials.
Keywords: E31; E44; E52; 330; Inflationsrate; Energiepreis; Lebensmittelpreis; Inflationsrate; Energiepreis; Lebensmittelpreis